Strategi Negara Indonesia dalam Menghadapi Ancaman Resesi Global - Tri Ayu Widyastuti (Sahmiyya, 2023)
This study aims to explain the strategy of the Indonesian state in facing the threat of a global recession. This study uses a descriptive qualitative method based on literature studies. Sources of data for this research come from journals and other literature related to recession, the potential for Indonesia to experience a recession, and Indonesia's strategy to face the threat of a global recession. Analysis of research data using VOSviewer - Visualization of scientific landscapes. The findings in this literature review study conclude that prolonged inflation, excessive deflation, asset bubbles by investors, unexpected economic shocks, excessive debt, and changes in technology can cause a recession. There are four main reasons for the 2023 recession including the impact of global economic conditions, rising bank interest rates, food and energy difficulties, as well as food instability and increasing debt. Indonesia will survive from the brink of recession if it can maintain its economic projections. Until now, Indonesia still holds tightly to the word potential in every news report on the 2023 recession, which means that it is still on alert and has a smaller probability of occurrence compared to other countries. To face the potential for a recession in 2023 by preparing insurance, both in the scope of health, life and vehicle insurance. Avoid long-term debt, because bank interest rates will experience a significant increase. In the face of a recession, we must continue to develop ourselves and learn new skills that will enable us to get a new job. Don't panic about investing, look for alternatives to supplement your income beyond the basic salary. Minimizing non-essential expenses can also be an effort to deal with a recession.